Antifungal activity of ZnO thin films prepared by glancing angle deposition - Pereira-Silva, Patrícia (2019)
Thin films of zinc oxide (ZnO) were produced by reactive DC magnetron sputtering with incidence angles of α = 0°, 40°, 60° and 80° (glancing angle deposition configuration), aiming to be tested against the opportunist pathogenic fungus Candida albicans. The results showed the formation of stoichiometric ZnO thin films, with inclined columns for incidence angles equal to or >40°. All thin films presented high transparency in the visible range above the bandgap region (near 380 nm). The deposition conditions gave rise to a three-fold increase of the surface porosity with the increment of the incidence angle. Noteworthy, is the formation of different types of pores distributions, from micro-, through meso-, to macropores. Regarding the biological effect, the thin films produced with inclined columns presented a significant antifungal activity, with the inhibition of viable cell growth by 68%. Moreover, the formation of mesoporous films enhanced the antifungal properties of ZnO thin films against Candida albicans. The overall behaviour indicates that these thin films are promising candidates to be applied in antimicrobial surfaces, as well as to be used in further studies to determine the molecular mechanisms involved in the antimicrobial action of ZnO.